Plausibility designs, or a probabilistic and predictive take on scenario effectiveness. (March 2021) - Janasik, Nina
Highlights: Plausibility and subjective probability can be integrated in a way that respects plausibility research as well as recent probabilistic developments in cognitive science. In the synthetic view, plausibility as the occurrability of some action or event is not the opposite of probability, but an integral part of the human cognitive dynamics of prediction and precision. Plausibility as occurrability is the measure of confidence (i.e. precision) that we have in our probabilistic predictions not being wrong in relation to action in some specific environment. The two notions are interdependent in that it is not possible to assess an action or event as plausible without this action or event having at least some minimum degree of prior expected (i.e. subjective) probability. The effectiveness of a scenario depends on how it is constructed in terms of the dynamic interplay between probabilistic prediction and plausibilistic precision. Abstract: Plausibility is often defined in direct contrast with probability. A common stance is that plausibility is a good ally of specifically social scientific studies of the future. A recent version of this claim is that scenario effectiveness is the result of plausibility ascription, not of the scenario narratives themselves, however, but of the "co-conversation" between the builders and users of scenarios. In this approach, probability falls out as redundant. Interestingly, this has striking similarities with recent probabilistic developments in cognitive literary studies. This approach claims that our judgments of the "effectiveness" of a literary text are dependent upon both the workings of our probabilistic, predictive minds during the reading process, and the "ease" with which we do such predictions. In this approach, however, there is little room for plausibility. In this paper, I argue that these two perspectives can be combined into a synthetic approach, which views the plausibility of a scenario co-conversation as an outcome of the "ease" with which scenario users "read" the scenario texts based on the workings of their probabilistic minds. Not only is this in line with recent results in cognitive science. It also holds promise of relieving the current tension between plausibility and probability in futures studies.